Growth and survivorship of Vetiveria zizanioides in degraded soil by gold-mining in the Peruvian Amazon - Jorge Santiago Garate-Quispe; Rosa Ponce de Leon; Marx Herrera-Machaca; Edgar Julian-Laime; Carlos Nieto-Ramos (Journal of Degraded and Mining Lands Management, 2021)
In the Peruvian Amazon, large area of primary forest have been deforested by Artisanal and small-scale gold mining (ASGM). Vetiveria zizanioides (Poaceae) is considered an excellent plant for the ecological restoration of degraded lands. The present study aimed to analyze the growth and survivorship of V. zizanioides in degraded soils by gold-mining in the Peruvian Amazon (Madre de Dios). The experiment was conducted under greenhouse conditions, and it followed a randomized complete block design with four treatments (substrates). The substrates were sand (mining), sand+pebbles (mining), forest soil, and amended soil. We evaluated the survivorship, shoot, tiller, and biomass production of V. zizanioides for two months. Univariate analysis of variance was used to detect differences among treatments. Fifteen days after experiment establishment, V. zizanioides survivorship was significantly higher in ASGM substrate 2 (sand+pebbles) than in other substrates, following the order of ASGM substrate 1 (sand) > forest soil > amended soil. However, at the end of the experiment, we did not find a significant difference on survivorship in subsequent assessments, and the total biomass per plant was lower in mining substrates than in non-mining substrates. The total biomass was significantly higher in amended soil than in other substrates, with yields between 1.7 and 3.6 times more biomass in amended substrate than in mine substrates. The soil substrate type significantly affected the survivorship, number of shoots, and biomass of V. zizanioides. The research results can provide a reference for remediation of degraded soils by gold-mining in the Peruvian Amazon.